2007
DOI: 10.1088/0957-4484/18/5/055402
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent (CdSe)ZnS quantum dot–polymethylmethacrylate polymer composite thin films in the visible spectral range

Abstract: We synthesized (CdSe)ZnS quantum dot (QD)–polymethylmethacrylate (PMMA) polymer composite and fabricated QD–polymer composite films. We produced the CdSe and (CdSe)ZnS QDs by direct colloidal chemical synthesis and the surface-passivation method—an overcoating of the dots with a larger-bandgap material. PMMA is transparent in the visible spectral range and was chosen as the embedding matrix for QDs. A 28%(wt/wt) of PMMA in MMA was the most appropriate concentration to produce a film of good quality and maximiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 15 publications
1
48
0
1
Order By: Relevance
“…Walker et al first characterized the temperature response of the photo-luminescence (PL) of colloidal QDs immobilized inside a polylaurylmethacrylate (PLMA) matrix [10] proving the suitability of QDs as temperature references for PL-based sensing applications. Other authors have also reported the use of different host polymers such as polystyrene (PS) [11] or polymethylmethacrylate (PMMA) [12] to embed QDs, and even coupling the light with the aid of optical fibers [13]. All these works use the PL of QDs as the sensing parameter, but none of them integrate the PL response into an optical waveguide, which is the key step to develop a temperature sensor into a photonic device.…”
Section: Introductionmentioning
confidence: 99%
“…Walker et al first characterized the temperature response of the photo-luminescence (PL) of colloidal QDs immobilized inside a polylaurylmethacrylate (PLMA) matrix [10] proving the suitability of QDs as temperature references for PL-based sensing applications. Other authors have also reported the use of different host polymers such as polystyrene (PS) [11] or polymethylmethacrylate (PMMA) [12] to embed QDs, and even coupling the light with the aid of optical fibers [13]. All these works use the PL of QDs as the sensing parameter, but none of them integrate the PL response into an optical waveguide, which is the key step to develop a temperature sensor into a photonic device.…”
Section: Introductionmentioning
confidence: 99%
“…plastics was investigated [391][392][393] A further elegant route to surface-functionalized ZnS nanoparticles (NPs) to be embedded in polymer matrix was based on a facile ligand exchange approach of mercaptoethanol with 5-(2-methacryloylethyloxymethyl)-8-quinolinol (MQ) [278]. By exploiting in situ bulk polymerization, the functionalised MQ-ZnS NPs were successfully incorporated into the polymer matrix to fabricate transparent bulk nanocomposites with good thermal stability and processability.…”
Section: Zinc Sulphidementioning
confidence: 99%
“…In the literature are however reported several examples of stable derivatisation of ZnS colloids, and hereafter some of the most meaningful ones are reported. Recently, the incorporation of ZnS:Mn NPs into polymeric matrix (polyacrylic acid and polymethylmethacrylate) to convey luminescent properties to plastics was investigated [391][392][393], although no specific functions by the polymers were demonstrated to enhance the interactions with the NPs. Alternatively, semiconductor nanocrystals (entirely or partially constituted by sulphides) were successfully incorporated into polymeric matrices [394] or derivatised with oleic acid and hexadecyl-trimethylammonium bromide to allow their dispersion in organic phases.…”
Section: Zinc Sulphidementioning
confidence: 99%
“…Walker et al first characterized the temperature response of the photo-luminescence (PL) of colloidal QDs immobilized inside a polylaurylmethacrylate (PLMA) matrix [10] proving the suitability of QDs as temperature references for PL-based sensing applications. Other authors have also reported the use of different host polymers such as polystyrene (PS) [11] or polymethylmethacrylate (PMMA) [12] to embed QDs, and even coupling the light with the aid of optical fibers [13]. All these works use the PL of QDs as the sensing parameter, but none of them integrate the PL response into an optical waveguide, which is the key step to develop a temperature sensor into a photonic device.…”
Section: Discussionmentioning
confidence: 99%
“…Walker et al caracterizaron por primera vez la respuesta con la temperatura de la fotoluminiscencia (en adelante PL, Photoluminescence) de QD coloidales inmovilizados dentro de una matriz de polilauril metacrilato (PLMA) [Walker03], demostrando la idoneidad de los QD como sensores de temperatura para aplicaciones de sensado basadas en PL. Otros autores también han informado del uso de diferentes polímeros como material base tales como poliestireno (PS) [Valerini05], o polimetil metacrilato (PMMA) [Song07] para embeber los QD, e incluso se ha utilizado la ayuda de fibra óptica para llevar a cabo el acoplo de luz [Jorge05]. Todos estos trabajos usan la PL de los QD como el parámetro de sensado, pero ninguno de ellos integra la respuesta de PL en una guía de ondas óptica, que es el paso clave para desarrollar un sensor de temperatura en de un dispositivo fotónico.…”
Section: Introductionunclassified